Anatomy of a misfit - Portes, Andrea (New York : HarperTeen, 2014)
The third most popular girl in school's choice between the hottest boy in town and a lonely but romantic misfit ends in tragedy and self-realization.
Keywords: Popularity -- Juvenile fiction; Love stories